Toxicity effects of some heavy metals on the growth of alga Scenedesmus dimorphus - Baghdad Science Journal (مجلة بغداد للعلوم)
The toxicity effect of some heavy metals (Lead, Cadmium, Copper, and Zinc) on the growth of alga Scenedesmus dimorphus which belongs to the Division of Chlorophyta was studied and depended on the total cell number . The growth rate and doubling time were also calculated accordingly in present of absent of the the heavy metals . There were differences in toxic effects of the metals (p